Carbo-loading in Coccidioides spp.: A quantitative analysis of CAZyme abundance and resulting glycan populations. (6th November 2019) - Mitchell, Natalie M; Grys, Thomas E; Lake, Douglas F
Abstract: Coccidioides spp . are important pneumonia-causing pathogens of the American southwest, but little is known about their glycobiology and how their glycosylations differ from other pneumonia-causing fungi. There is mounting preliminary evidence to suggest genus or even species-specific glycosylations in the fungal kingdom due to the presence of unique carbohydrate-active enzymes (CAZymes) in fungal genomes (Deshpande et al. 2008, Glycobiology, 18(8), 626–637; Karkowska-Kuleta and Kozik 2015, Acta Biochim Pol., 62(3), 339–351). If Coccidioides spp .- specific glycans can be identified, it may be possible to exploit these differences to develop more specific diagnostic approaches and more effective therapeutics. Herein, we i) mined Coccidioides spp. and other pathogenic fungal genomes to identify CAZymes specific for Coccidioides spp., ii) proteomically determined the Coccidioides spp . "CAZome" produced in vivo and in vitro, and iii) utilized glycomics to differentiate Coccidioides genus-specific N-glycans from other pathogenic fungi. As far as we are aware, this is the first proteomic and glycomic comparison of the N-glycomes and CAZomes of different fungal genera during infection in human hosts.